Pengaruh Harga dan Keragaman Produk terhadap Keputusan Pembelian - Diantanti, Novita Putri; Pradeta, Fandu Dyangga; Natasya, Vani (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2022)
The automotive world has its own value for its customers so that many open Showroom businesses, one of which is the Putri Motor Showroom which is a place to buy and sell used cars that are crowded with consumers' interest. Seeing the crowded Putri Motor Showroom is the reason this research was conducted to see the influence of price and product diversity on purchasing decisions at the Putri Motor Showroom. The research approach is through quantitative, because it aims to prove the hypothesis with instruments that become a research tool carried out through survey methods. The research was carried out at the Putri Motor Showroom which was addressed in Garum District, Blitar Regency by distributing questionnaires. In this study, customers at the Putri Motor Showroom with a total of 36 people for one year were sampled. It is known that the results of research on price variables and product diversity both partially and simultaneously influence the purchase decision at the Putri Motor Showroom.